IMPLEMENTASI KURIKULUM PESANTREN PADA PEMBELAJARAN FIQIH DI MADRASAH TSANAWIYAH ISLAMIYAH (MTI) CANDUANG - Ummil Khairat; Iga Permata Sari; Melati Puspita; Salsabilla Ratu Faizah (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This study examines the implementation of dual curriculum in Fiqih learning at MTI Canduang Islamic Boarding School, an Islamic educational institution that integrates traditional pesantren heritage with modern educational demands. Through in-depth interviews with three key informants—the Vice Curriculum and two Fiqih teachers—the research reveals the complexity of contemporary pesantren educational dynamics. Findings indicate that MTI Canduang successfully integrates the hereditary pesantren curriculum with the Ministry of Religious Affairs curriculum. The research explores pedagogical strategies, innovative methods of teaching kitab kuning (classical Islamic texts), and challenges in the digital era. The uniqueness of this study lies in revealing the Mifta Al-Qulum method, a local innovation to accelerate the understanding of kitab kuning, as well as translation practices based on i'rab meaning that characterize this pesantren. The research results provide important contributions to the development of pesantren educational models capable of maintaining the authenticity of Islamic scholarly traditions while adapting to contemporary developments.